1991
DOI: 10.1104/pp.95.3.753
|View full text |Cite
|
Sign up to set email alerts
|

N2-Fixation by Freshly Isolated Nostoc from Coralloid Roots of the Cycad Macrozamia riedlei (Fisch. ex Gaud.) Gardn.

Abstract: Nitrogenase (EC 1.7.99.2) activity (acetylene reduction) and nitrogen fixation (15N2 fixation) were measured in cyanobacteria freshly isolated from the coralloid roots of Macrozamia riedlei (Fisch. ex Gaud.) Gardn. Light and gas phase oxygen concentration had marked interactive effects on activity, with higher (up to 100-fold) rates of acetylene reduction and 15N2 fixation in light.The relationship between ethylene formation and N2-fixation varied in the freshly isolated cyanobacteria from 4 to 7 nanomoles of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…The symbiotic condition of Nostoc witbin host cells appears to provide a micro-aerobic environment not unlike that of the legutne nodule, in which the isolated bacterium is quite unprotected from oxygen. Tbis is in contrast to the cycad isolates (Lindblad, Atkins & Pate, 1991) wbicb appear to tolerate a low oxygen tension.…”
Section: Discussionmentioning
confidence: 96%
“…The symbiotic condition of Nostoc witbin host cells appears to provide a micro-aerobic environment not unlike that of the legutne nodule, in which the isolated bacterium is quite unprotected from oxygen. Tbis is in contrast to the cycad isolates (Lindblad, Atkins & Pate, 1991) wbicb appear to tolerate a low oxygen tension.…”
Section: Discussionmentioning
confidence: 96%
“…However, the cyanobionts from cycads and Gunnera require microaerobic conditions in which to fix N # (Lindblad et al, 1991 ;Silvester et al, 1996). It is uncertain what changes have occurred in these heterocysts to make them oxygen-sensitive.…”
Section: Modifications Of the Cyanobiontmentioning
confidence: 99%
“…Although the cyanobionts develop heterocysts, these are not able to provide nitrogenase with protection from oxygen. Cyanobionts freshly isolated from roots or glands require microaerobic conditions to fix N # (Lindblad et al, 1991 ;Silvester et al, 1996). In symbiosis with diatoms, the cyanobiont Richelia does not seem to produce gas vesicles and might therefore decrease its energy costs by depending on the host for buoyancy.…”
Section: Benefits To the Partnersmentioning
confidence: 99%
“…A total of 24 endosymbiont species, mostly Nostoc spp., were recently isolated from the coralloid roots of 74 cycad plants (Gehringer et al, 2010). It has been previously demonstrated that the symbiotic cyanobacteria in Macrozamia riedlei, while photosynthetically inactive, fixed nitrogen and transferred it to the host cycad plant in the form of citrulline and glutamine (Lindblad et al, 1991). Microcystin-producing Nostoc symbionts of lichens have also been identified (Oksanen et al, 2004;Kaasalainen et al, 2009), with both strains producing several variants of microcystin.…”
Section: Introductionmentioning
confidence: 99%